Professional Roles in News Content: Six Dimensions of Journalistic Role Performance - Mellado-Ruiz, C (Routledge, 2015)
Over the past 50 years, a large body of research on professional roles has analyzed the different functions that journalism should fulfill in society. However, an examination of how these professional roles materialize in journalistic output remains mostly absent. This is especially critical because most studies of journalists attitudes are justified by assuming that they influence news content. By combining the study of news content with research on professional roles, this study proposes a standardized operationalization of how different professional roles can manifest in journalistic performance. Specifically, this paper connects the characteristics of professional roles that have been studied in comparative contexts with different journalistic discourses and reporting styles in news, considering the relationship between journalism and power, the level of presence of the journalistic voice in a story, and the way journalism approaches the audience. © 2014 Taylor & Francis.